Dipolar Cycloaddition-Based Multicomponent Reactions in Ionic Liquids: A Green, Fully Stereoselective Synthesis of Novel Polycyclic Cage Systems with the Generation of Two New Azaheterocyclic Rings - Kumar, Raju Suresh; Almansour, Abdulrahman I.; Arumugam, Natarajan; Menéndez, J. Carlos; Osman, Hasnah; Kumar, Raju Ranjith (Synthesis, 2015)
Two libraries of novel, bifunctional polycyclic cage structures have been synthesized for the first time in an ionic liquid, 1-butyl-3-methylimidazolium bromide ([bmim]Br), employing a sustainable microwave-assisted, one-pot, three-component [3+2] cycloaddition–annulation protocol in good to excellent yields. The ring systems thus generated contain as structural elements bridged, fused and spiro rings and were obtained with complete regio- and stereoselectivity through the creation of two C–C and two C–N bonds, which led to the generation of two azaheterocyclic rings and five adjacent stereogenic carbons, three of which are quaternary.
Keywords: azomethine ylides; [3+2] cycloadditions; ionic liquids; stereoselective synthesis; spiro compounds